Integrasi Nilai Akhlak Mulia dalam Budaya Minangkabau Pada Mata Pelajaran PAI BP - Ermiyanto; Fadriati (Prodi Pendidikan Agama Islam, 2023)
Character education in educational institutions is the foundation in moral development. Islamic Religious Education Materials (PAI) and Budi Pekerti (BP) are learning materials that are very relevant to moral development in schools. Moral learning cannot be separated from the culture of the school environment. Minangkabau culture that developed through Islamic culture has moral values ​​as evidenced by several moral terms that are relevant to Minangkabau expressions. The integration of PAI BP learning with Minangkabau culture needs to be done in the context of developing and strengthening the morals of students. The method used in this study is a literature review sourced from 15 national journals and 3 international journals published between 2018 and 2022. The journals were selected from Google Schoolar with the keywords